PERLINDUNGAN HUKUM PEKERJA WANITA TERHADAP SISTEM PENGUPAHAN YANG LAYAK SEBAGAI REFLEKSI HUBUNGAN INDUSTRIAL YANG SELARAS DAN SERASI - Mirwansyah Mirwansyah (Universitas Sang Bumi Ruwa Jurai, 2018)
Employment is an incessant constitutional issue The employment cases spread across the country, such as labor strikes due to low wages and benefits not granted or met by the company, termination of employment committed by the company on the grounds efficiency of employment without severance pay, employment for days to be sent out of the country without feeding and daily necessities, fraud of prospective workers by paying some millions of rupiah administration money by fictitious and discriminatory companies against women workers. As one aspect of development, the workforce needs protection in all aspects, including protection of employment at home and abroad, protection of basic rights, protection of occupational safety and health, non-discrimination protection and wage protection and so on. In addition to the remuneration of the worker, in the case of an employer allowance shall be obligated to provide to his workers, as stipulated in the Regulation of the Minister of Manpower No.. 6 Year 2016 on Religious Days Allowance For Workers / Workers in Company. The current labor problem continues to grow especially for women and therefore requires a more serious handling despite the direction and implementation of Law Number. 13 of 2003 on Employment is implicitly existing in providing protection to workers, especially women workers, legal protection efforts are done by prevention (preventive) and repression (repressive). Countermeasures are done by way of socialization to the community, but in its implementation there are still many women workers who do not know and understand the rules that apply. When we look, the existing labor regulations still place the workforce in an unfavorable position. With the various phenomena above, we expect the Law Number. 13 of 2003 on Manpower (hereinafter abbreviated as UUKK) and other regulations may restore the image of Indonesian employment so that the problems of employment can be overcome well which finally creates the protection of women workers law against the proper wage system as a reflection of harmonious and harmonious industrial relations especially the balance between employers and workers.Efforts to protect the law is done by prevention (preventive) and repression (repressive). Handling is done by way of socialization to the community. Although the government has done a lot of actions, but the efforts made by the Indonesian government in the framework of the protection of this workforce has not produced maximum results.